Effect of chlorine, sulfur, moisture and ash content on the partitioning of As, Cr, Cu, Mn, Ni and Pb during bituminous coal and pickling sludge co-combustion. (1st March 2019) - Zhang, Shaorui; Jiang, Xuguang; Lv, Guojun; Nixiang, Abulaiti; Jin, Yuqi; Yan, Jianhua; Lin, Xuliang; Song, Huibo; Cao, Junjun
Highlights: Co-combustion study was performed at similar temperature condition of suspension firing boilers. More than 99% of Cr and Ni were retained in bottom ash and not affected by these four additives. As percentage in bottom ash was reduced obviously by all additives addition except kaolin. Cu and Pb percentage in bottom ash was ash reduced by NaCl addition while increased by FeS2 addition. Abstract: The effect of chlorine, sulfur, moisture and ash content in blended fuels on the partitioning of As, Cr, Cu, Mn, Ni and Pb during bituminous coal and pickling sludge co-combustion were studied in a horizontal tube furnace. Additives including NaCl, FeS2, water and kaolin were used to simulate coal with high chlorine, sulfur, moisture and ash content, respectively. The percentage of pickling sludge used in all conditions was 10%, and the additives added range was 1%–20%. The experimental results indicated that with increasing NaCl addition the percentage of As, Cu and Pb in bottom ash decreased significantly and the Mn percentage in fly ash increased slightly. Under FeS2 addition condition, Cu and Pb percentage in bottom ash increased significantly due to the incomplete decomposition of the generated CuFe2 O4 and PbSO4 while the volatilization of As was promoted. With the increasing addition of water, a higher percentage of As moved into the fly ash from bottom ash, while the proportion of Pb in the fly ash decreased obviously. Under kaolin addition, the As partitioning showed a fluctuation trend, while for Pb and Cu the adsorption was the main effect and their distribution in bottom ash increased. Under all conditions, Cr and Ni partitioning were not affected by additives due to the non-volatility and stability of Cr, Ni and their compounds. Bottom ash XRD analysis results showed that CaF2 disappeared under NaCl addition condition and lots of Ca2 Al2 SiO7 generated. In addition, FeS2 addition caused more CaSO4 generated due to the sulfation reaction, while no obvious change of bottom ash composition was found under neither water nor kaolin addition.